PENGARUH METODE PROJECT BASED LEARNING TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 1 PENANGGALAN KOTA SUBULUSSALAM - Atmiarti, Atmiarti; Padlurrahman, Padlurrahman; Khaerul Wazni, Muhammad (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
The aim of this research was to determine the effect of constructive play and linguistic intelligence on the beginning reading abilities of children aged 5-6 years at Pembina Kindergarten, Labuhan Haji District. The type of research used is quantitative research with an experimental research method with a 2 x 2 level treatment design. The population of this research is all 28 children in Kindergarten Pembina, the sampling technique is a multistage random sampling technique. Data analysis techniques use descriptive statistics and inferential statistics. Meanwhile, inferential statistical analysis takes the form of a two-way ANOVA test and a Tukey test with a significance level of α=0.05. The results of this study show that there is an influence of constructive games and linguistic intelligence on initial reading ability with a two-way ANOVA test of fcount= 22,443 > ftable= 4.26. In addition, F (OAB) = 4.690> ftable = 4.26. There is an interaction between constructive play and cognitive style on children's beginning reading abilities with fcount = 300,171 > ftable = 4.26. Based on the results of the Tukey test, Qcount A1B1 = 22.07 > Qtable = 4.60. Tukey test results obtained Qcount A2B2 = 12.59 > Qtable = 4.60. This shows that the group of children who have linguistic intelligence, the beginning reading abilities of children who are given constructive play with image media, H1 in each hypothesis is accepted.